Marine Tourism Potential of Jikomalamo Beach Ternate, North Maluku Province - A. Gani, Rivaldi; Bagus Sasrawan Mananda, I Gusti Putu; Adikampana, I Made (Asian Journal of Social and Humanities, 2024)
This research aims to assess the potential and governance of tourism to formulate participation management strategies for the marine touris attraction of Jikomalamo Beach in Ternate. Data for this research were obtained through observation methods, focus group discussions, and in-depth interviews. The data were analyzed using qualitative descriptive analysis, IFAS, EFAS analysis, and SWOT analysis, which resulted in participation management strategies. The results of this research shows that the strengths of Jikomalamo management include community participation in destination management, potential for underwater tourism, management of water sport facilities, and the existence of a dive center management. Meanwhile, the weaknesses of Jikomalamo Ternate include the absence of a tourism management organization (pokdarwis), lack of management of human resources quality, lack of stakeholder involvement, and the absence of a tourist information center. Based on the Internal External (IE) matrix, it is known that the position of Jikomalamo Beach management is in quadrant one which is strong. where the strategy used is Growth strategy. Based on the SWOT analysis, it is known that there are six alternative participatory management strategies to be applied, namely community engagement strategy, human resource development, establishment of management organizations, collaboration among stakeholders, and improvement of tour packages.